Topical delivery of ebselen encapsulated in biopolymeric nanocapsules: drug repurposing enhanced antifungal activity. (6th June 2018) - Jaromin, Anna; Zarnowski, Robert; Piętka-Ottlik, Magdalena; Andes, David R; Gubernator, Jerzy
Aim: Ebselen (Eb) is an example of a repurposed drug with poor aqueous solubility which requires sophisticated delivery system such as nanoencapsulation in nanocapsules for topical application.Materials & methods: Eb-nanocapsules were examined for morphology, activity against Candida spp., cytotoxicity and skin permeation.Results: Eb-nanocapsules were active against skin-infecting Candida tropicalis, Candida albicans and Candida parapsilosis yeasts (minimal inhibitory concentration values were about 4-, 2- and 1.25-times lower vs free Eb, respectively) and able to suppress induced lipid oxidation in the oil/water emulsion. Moreover, demonstrated minimal toxicity in normal human dermal fibroblast cell line, whereas ex vivo skin permeation studies showed no transdermal passage and strong interactions with stratum corneum.Conclusion: Eb-nanocapsules represent a promising, safe and complementary alternative to the treatment of cutaneous candidiasis.